Incidental Experiences of Affective Coherence and Incoherence Influence Persuasion. (June 2013) - Huntsinger, Jeffrey R.
When affective experiences are inconsistent with activated evaluative concepts, people experience what is called affective incoherence ; when affective experiences are consistent with activated evaluative concepts, people experience affective coherence. The present research asked whether incidental feelings of affective coherence and incoherence would regulate persuasion. Experiences of affective coherence and incoherence were predicted and found to influence the processing of persuasive messages when evoked prior to receipt of such messages (Experiments 1 and 3), and to influence the confidence with which thoughts generated by persuasive messages were held when evoked after presentation of such messages (Experiments 2 and 3). These results extend research on affective coherence and incoherence by showing that they exert a broader impact on cognitive activity than originally assumed.